Caracterização morfológica do diásporo e da plântula de Archontophoenix cunninghamii (Arecaceae) - Da Luz, Petterson Baptista; Pivetta, Kathia Fernandes Lopes [UNESP]; Neves, Leonarda Grillo; De Paiva Sobrinho, Severino; Barelli, Marco Antonio Aparecido (My University, 2012)
The palm Archontophoenix cunninghamii H.Wendl. & Drude, even widely used in landscaping, has been poorly studied. In general, there are few articles on morphology of seeds and seedlings of Arecaceae species. With the aim of filling this gap, the objective of the present work describes the diaspore (seed with adhering endocarp) and the seedling morphology. A. cunninghamii seeds present rounded shape and a ruminated endosperm of hard consistency. The embryo is lateral, peripheral and relatively undifferentiated, approximately 4 mm long, conical, with one of the extremities convex, and in its inside there is a small protuberance while the other extremity is rounded and narrower. The seedling is adjacent ligulated and hypogeal, with the development starting from a mass of undifferentiated cells in the micropillar depression, the differentiation of shoot and root primordium, being the first enveloped by a sheath closed. The root system is fasciculate, with different adventitious roots and several lateral roots with few absorbent hairs. The stem comprises three sheaths surrounding the first young leaf, which are opened in succession, permitting the emergence of the primary bifid leaf, with typical parallel nerves.
Morphological characterization of Archontophoenix cunninghamii (Arecaceae) diaspores and seedlings
Keywords: Australian royal palm; Seed germination; Seeds